Addressing the healthcare waste management barriers: A structural equation modeling approach - Raj A.; Samuel C.; Singh A.K. (My University, 2025)
Due to the growing population and advancing economy, medical waste accumulation has come to the attention of all facets of society. Although the issue of medical waste management planning has been addressed in developed nations, it still exists in several developing nations. This paper examines the effects of barriers under the Organization action, work handling, and Human Resource Practices section on the healthcare waste management (HCWM) sector in a developing country India. In this study, three hypotheses were constructed and tested using Structural equation modeling. The questionnaire was distributed among 200 health professionals to collect their responses. Ninety-seven responses were received, and 15 barriers were identified affecting the healthcare waste management sector. The results show that all three barriers (i.e., Organizational, Waste handling, and Human resources) hinder the Healthcare waste management sector. Organizational Barriers are the most significant among other barriers. So, the hospitals have to take appropriate actions to overcome these barriers. This paper helps to complete the research gap by providing the different characteristics of barriers. The development of a model for the analysis of barriers influencing HCWM is the Author’s original contribution. © The Author(s) 2023.